The Legal and Political, Government Support Affecting Factors on the Implementation of Public-Private Partnerships in Residential Investment Ventures (Journal of Engineering, 2025)
In several developing countries, the increasing request for housing and budgetary constraints have directed governments to search new ways of housing delivery. Many governments adopted an option partnership with the private sector commonly referred to as Public Private Partnership (PPP). The purpose of this study was to investigate the most important legal and political, government support Factors affecting the Implementation of PPPs in residential investment ventures in Iraq thereby reducing the housing deficit in the country. An inclusive research technique comprising a written review, interviews/discussions with decision-makers, professional experts, and seasoned practitioners, as well as a questionnaire, was used to extract the data for this study. One hundred questionnaire models were sent to public institutions, private sector companies, and government agencies. The responses were then subjected to statistical analysis. The outcomes show that the most five important legal and political factors were inefficiency/efficient legal framework with (Relative Important Index) RII=0.79; unstable/Stable political system with RII=0.79; corruption with RII=0.78; the growing phenomenon of partisanship with RII = 0.78; Commitments of the public and private sector with RII=0.77. While that the most five important government support Factors were Land acquisition with RII=0.77; Grants with other forms of financial support loans with RII=0.76; Government's supportive stance on investments from the private sector with RII=0.75; Project Ownership Issues with RII=0.73; Relief in certain Force Majeure events with RII=0.72 this factors can be taken in consideration for making any investment decision.